The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1111/j.1365-2753.2012.01848.x
|View full text |Cite
|
Sign up to set email alerts
|

Adapting low back pain guidelines within a multidisciplinary context: a process evaluation

Abstract: The AAP successfully utilized existing stakeholder interest to create an overarching guideline for managing LBP across multiple primary care disciplines. The study highlighted the strengths and weaknesses of the Program, and identified practical strategies for improvement. Evaluating guideline adaptation processes is pivotal to ensuring that they continue to be an efficient, rigorous and practicable option for producing contextualized, clinically relevant guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 22 publications
(32 reference statements)
2
8
0
Order By: Relevance
“…A survey by the G‐I‐N reported that the need for training, the complexity of the process, and the time needed to adapt a CPG are perceived as barriers to the use of a formal adaptation process . Similar barriers were identified elsewhere . Our observations are in line with the literature.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A survey by the G‐I‐N reported that the need for training, the complexity of the process, and the time needed to adapt a CPG are perceived as barriers to the use of a formal adaptation process . Similar barriers were identified elsewhere . Our observations are in line with the literature.…”
Section: Discussionsupporting
confidence: 93%
“…32 Similar barriers were identified elsewhere. 31,[33][34][35] Our observations are in line with the literature.…”
Section: Findings Related To Pilot Adaptationssupporting
confidence: 92%
“…Very similar barriers were identified by Harstall et al . in the evaluation of the Alberta Ambassador Project [24,29], by Chakraborty et al . [19] in Australia.…”
Section: Discussionmentioning
confidence: 99%
“…A survey by the Guideline International Network reported that the need for training, the complexity of the process and the time needed to adapt a CPG are perceived as barriers to the use of a formal adaptation process [31]. Very similar barriers were identified by Harstall et al in the evaluation of the Alberta Ambassador Project [24,29], by Chakraborty et al [19] in Australia. They were very much the same as those expressed by the participants involved in our process.…”
Section: Improving the Adaptation Processmentioning
confidence: 90%
“…The ADAPTE framework consists of 24 steps in three main phases: (1) set–up (preparation), (2) adaptation and (3) finalization [ 7 ]. The evaluation of guideline adaptation has been recommended to ensure the reproducibility and efficiency of the methods in producing high quality guidelines [ 8 ].…”
mentioning
confidence: 99%